"PCR- Detection of Candida albicans in Blood Using a New Primer Pair to Diagnosis of Systemic Candidiasis" - SH Mirhendi; K Makimura (Tehran University of Medical Sciences, 2003)
The opportunistic pathogen C.albicans is able to cause disseminated infections in immunocompromised patients. Microbiological methods for the diagnosis of invasive candidiasis have many problems including low sensitivity, requirement to invasive clinical sampling such as biopsies or multiple blood cultures and need to expertise laboratory stuff. Since PCR has proven to be a powerful tool in the early diagnosis of several infectious diseases, we applied this approach as a rapid and sensitive method in detection of C.albicans cells in blood samples, for establishment a clinically useful method in diagnosing systemic candidiasis. DNA were extracted from blood samples seeded by serially diluted C.albicans cells, by omitting WBC and RBC followed by enzymatic breaking of fungal cell wall and phenol - chlorophorm extraction and alcohol precipitation of DNA. A new primer pair was designed for PCR-amplification of a part of ribosomal RNA gene. The primer set was able to amplify all medically important Candida species. When PCR was performed for detection of purified DNA, the sensitivity of the method was about 1 picogram fungal DNA, whereas the sensitivity for detection of C.albicans blastospores inoculated in blood was as few as 10 cell per 0.1 ml of blood. This method could be sensitive and useful for early and rapid diagnosis of systemic Candida infections and to simultaneous detection and speciation of Candida species by PCR-RFLP method.